The book of papercutting : a complete guide to all the techniques with more than 100 project ideas - Rich, Chris, 1949- (New York : Sterling Pub. Co., 1993)
A complete guide to all the techiques with more than 100 project ideas.--Title page.
"A Sterling/Lark book."
Includes bibliographical references (p. 127) and index.
Wilson's Junior High School
School Library Journal
Booklist
Adult
Keywords: Paper work; Paper crafts